2013
DOI: 10.7314/apjcp.2013.14.9.5367
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Esophageal Cancer Incidence in Tehran by Log-linear Method using Population-based Cancer Registry Data

Abstract: Background: Having knowledge or estimation of cancer incidence is necessary for planning and implementation of any cancer prevention and control programs. Population-based registries provide valuable information to achieve these objectives but require extra techniques to estimate the incidence rate. The present study aimed to estimate the esophageal cancer incidence using a log-linear method based on Tehran population-based cancer registry data. Materials and Methods: New cases of esophageal cancer reported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…The mean age of all subjects was 66.68 ± 13.23 years (67.60 ± 12.91 for men and 65.48 ± 13.58 for women). The age distribution does not show the difference between men and women and slightly higher than the average age reported by studies conducted in other parts of Iran that reported average age 58 - 65 years for esophagus cancer ( 17 - 19 ), but reported average age in the study conducted in Tehran metropolitan was 70.40 (70.5 for men and 70.3 for women) that is slightly higher than present study ( 7 ). Male to female ratio was 1.29 that is consistent with international and regional reports ( 2 , 7 , 20 ).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The mean age of all subjects was 66.68 ± 13.23 years (67.60 ± 12.91 for men and 65.48 ± 13.58 for women). The age distribution does not show the difference between men and women and slightly higher than the average age reported by studies conducted in other parts of Iran that reported average age 58 - 65 years for esophagus cancer ( 17 - 19 ), but reported average age in the study conducted in Tehran metropolitan was 70.40 (70.5 for men and 70.3 for women) that is slightly higher than present study ( 7 ). Male to female ratio was 1.29 that is consistent with international and regional reports ( 2 , 7 , 20 ).…”
Section: Discussioncontrasting
confidence: 95%
“…Completeness is defined as the proportion of incident cancer cases that is registered ( 5 ). Completeness level of cancer registration is one of the main parts of quality control in such registration ( 7 ). Since most cancer registries employ more than one data source for case finding, capture-recapture methods may be used to estimate the number of incident cases in the population, and hence to assess completeness of case ascertainment ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noteworthy that our study population consisted of referred patients, and due to increasing medical centers in other provinces, reduced frequency of referred malignancy in the years 2000 onwards could be expected. The mean age of patients in the study of Mosavi was 70 years old and there was no difference in age between men and women in 2002-2006 but Sex ratio (male to female) was 1.3 (Mosavi-Jarrahi et al, 2013). In a study of Mansour-Ghanaei the mean age of patients was 63 between 1996 to 2005 (Mansour- .…”
Section: Discussionmentioning
confidence: 87%
“…ESCC is especially endemic in the Eastern Anatolian region of Turkey, as well as some parts of Iran, Afghanistan, Turkmenistan, Kyrgyzstan, Uzbekistan, India, China, and Latin America (Moore et al, 2010;Uyanikoglu et al, 2011;Mosavi-Jarrahi et al, 2013;Tang et al, 2013;De Stefani et al, 2014). In the present study, we compared the demographic features and nutritional habits of 208 ESCC patients in the Eastern Anatolian region with those of a control group, and we evaluated the results of our study in light of the current literature.…”
Section: Discussionmentioning
confidence: 99%